Best practices in teaching digital literacies - Ortlieb, Evan; Cheek, Earl H.; Semingson, Peggy, 1973- (Literacy research, practice and evaluation ;, 2018)
The almost universal reliance upon digitaltools for social, academic, and career development will only become morepronounced in the years to come. Teacher education programs remain ill-equippedto adequately prepare educators with the pedagogies needed to foster digitalliteracies. What is needed is a set of best practices towards teaching digitalliteracies so that teachers can better meet the emerging needs of theirstudents in todays classrooms. Where should teachers begin? What are theessentials of digital literacies within K-12 contexts? And how might wereimagine teacher education programs to optimally prepare teachers for workingwith technologically connected youth, whose literacies are more complex,interconnected, and diverse than ever? This volume provides a practicalframework for teacher education programs to develop K-12 students digitalliteracies. It offers a set of best practices in teaching digitalliteracies that promote access to research-based pedagogies for immediateimplementation in classrooms.